KEADAAN SOSIAL EKONOMI NELAYAN BAGAN DI KELURAHAN KOTA KARANG KOTA BANDAR LAMPUNG - Muhammad Yasir; Sudarmi Sudarmi; Zulkarnain Zulkarnain (JPG (Jurnal Penelitian Geografi), 2017)
This Study was aimed to find out Social and economic condition of bagan fisherman in Kota Karang Village, East Teluk Betung Subdistrict, Bandar lampung in 2016. Descriptive method was used in this study. There were 612 heads of family as the population with 10% of them were taken as the sample that is 61 heads of family. To collect the data, observation, interview, questionnaire, and documentation were used. The data were analyzed by percentage table.The Result showed that (1) The education level of the heads of family was still low with average graduates of elementary school and junior high school. (2) The age of the heads of family belonged to productive category. (3) The number of family dependants was indicated as a small family with the number of dependants which as less than 5. (4) Labor and trader turned to be side jobs done by fisherman. (5) The income level of bagan fisherman was low which was below avarege of income obtained by the whole fisherman.Penelitian ini bertujuan untuk mengetahui mengetahui keadaan sosial ekonomi keluarga nelayan bagan di kelurahan Kota karang Kecamatan Teluk Betung Timur Kota Bandar Lampung tahun 2016.Penelitain ini mengguankan metode deskriptif.Populasi penelitian ini sebanyak 612 orang, sampel 10% atau 61 orang.Pengumpulan data dengan teknik observasi, wawancara, kuesioner dan dokumentasi.Data dianalisis dengan tabel persentase.Hasil penelitian ini menunjukkan bahwa: (1) Tingkat pendidikan kepala keluarga nelayan bagan masih rendah. (2) Umur kepala keluarga nelayan bagan masih terbilang produktif. (3) Jumlah tanggungan kepala keluarga nelayan bagan merupakan keluarga kecil dengan jumlah tanggungan kurang dari 5. (4) sebagian nelayan bagan memliki pekerjaan sampingan yaitu sebagai kuli, tukang ojek dan berdagang. (5) pendapatan nelayan bagan tergolong rendah dengan pendapatan dibawah rata-rata pendapatan nelayan.Kata Kunci: nelayan, nelayan bagan, sosial ekonomi